Evaluate: $\displaystyle\int_{0}^{1}\frac{\ln(x+1)}{x^2+1}\,\mathrm{d}x$

So I did this a completely different way than what the answer key states. I used integration by parts and some symmetry tricks and got the correct answer. However the answer key says:

Make the substitution $x=\frac{1-u}{1+u}$

The same solution was reached in about half the steps but still using symmetry, my questions are How would I know to do that? Is this a certain type of substitution? Is there something else that maybe I could use this for?

  • $\begingroup$ the change of variable reminds me a bit the Weierstrass substitution $\cos(x)=\frac{1-t^2}{1+t^2}$ $\endgroup$ – Masacroso May 18 '17 at 20:31
  • $\begingroup$ That is true. The weierstrauss sub is actually what I used in part of my long solution $\endgroup$ – Teh Rod May 18 '17 at 20:33
  • 1
    $\begingroup$ The transformation is a Möbius Transform, not a Weierstrass substitution. $\endgroup$ – Mark Viola May 18 '17 at 20:39
  • $\begingroup$ possible duplicate math.stackexchange.com/questions/155941/… $\endgroup$ – Darío A. Gutiérrez May 18 '17 at 21:09

The substitution is called a Möbius Transformation, which has the more general form


where $ad\ne bc$. The transformation maps straight lines into circles and circles into straight lines. They have a variety of uses in applied mathematics and physics along with complex analysis.

As a simple example, the Beta function $B(x,y)$ can be represented by the integral

$$B(x,y)=\int_0^1 t^{x-1}(1-t)^{y-1}\,dt$$

Enforcing the Mobius Transformation $t\to \frac{t}{1+t}$ so that $dt\to \frac{1}{(1+t)^2}\,dt$. Then, we see that

$$B(x,y)=\int_0^\infty \frac{t^{x-1}}{(1+t)^{x+y}}\,dt$$

which is an alternative representation for the Beta function.

As another example, in This Question, the OP requested evaluation of the integral $I$ expressed as


In the accepted answer posted by User @FDP, the Mobius transform was used to facilitate an efficient way forward.

As a third and final example, in THIS ANSWER, I showed using only the limit definition of the exponential function and Bernoulli's Inequality that the exponential function satisfies the inequalities

$$1+x\le e^x\le \frac{1}{1-x}$$

for $x<1$. Then, it is trivial to see that $\log(x)\le x-1$.

Applying the Möbius Tranformation $x\to \frac{-x}{1+x}$ we find that the logarithm function is bounded below by $\log(x)\ge \frac{x-1}{x}$.


Here's an alternative method that doesn't use differentiation under the integral sign. Substitute $x = \tan \theta$, to give $$I = \int_0^{\pi/4} \log(1+\tan\theta) d\theta \\ = \int_0^{\pi/4} \log(\cos\theta+\sin\theta)-\log\cos(\theta)d\theta \\ = \int_0^{\pi/4} \frac12\log2 + \log(\cos(\theta- \pi/4))-\log\cos(\theta) d\theta \\ = \frac{\pi}{8}\log2 + \int_0^{\pi/4} \log(\cos(\theta- \pi/4)) d\theta - \int_0^{\pi/4}\log\cos(\theta) d\theta $$ We have the known property that $\int_0^a f(x) dx = \int_0^a f(a-x)dx$, and $\cos$ is an even function, so these two final integrals are equal, and $I = \frac{\pi}{8}\log2$.


Here's how I would do it. Let $$f(\alpha)=\int_0^1 \frac{\log(1+\alpha x)}{1+x^2}\ dx$$ where $f(1)$ is the integral we seek to evaluate. By differentiation under the integral sign we have $$f'(\alpha)=\int_0^1\frac{\partial}{\partial\alpha}\frac{\log(1+\alpha x)}{1+x^2}\ dx\\ =\int_0^1\frac{x}{(1+x^2)(1+\alpha x)}\ dx.$$

Now we apply partial fraction decomposition: suppose that $$\frac{x}{(1+x^2)(1+\alpha x)}=\frac{Ax+B}{1+x^2}+\frac{C}{1+\alpha x}$$ for some constants $A,B,C$. By combining the fractions and collecting the terms we obtain the linear system of equations $$\begin{cases}A+\alpha B=1\\ \alpha A+C=0\\B+C=0\end{cases}$$ which we find to be equivalent to $$\begin{cases}A=\frac{1}{1+\alpha^2}\\B=\frac{\alpha}{1+\alpha^2}\\C=-\frac{\alpha}{1+\alpha^2}\end{cases}$$ From this we conclude that $$f'(\alpha)=\int_0^1\frac{Ax+B}{1+x^2}+\frac{C}{1+\alpha x}\ dx\\ =\left[\frac12 A\log(1+x^2)+B\arctan{x}+\frac{C}{\alpha}\log(1+\alpha x)\right]_{x=0}^1\\ =\frac{\log2}{2}\frac{1}{1+\alpha^2}+\frac{\pi}{4} \frac{\alpha}{1+\alpha^2}-\color{red}{\frac{\log(1+\alpha)}{1+\alpha^2}}$$ It is easy to see by looking at the definition that $f(0)=0$. From this it follows that $f(\alpha_0)=\int_0^{\alpha_0} f'(\alpha)\ d\alpha$, and in particular $$f(1)=\int_0^1 \frac{\log2}{\alpha}\frac{1}{1+\alpha^2}+\frac{\pi}{4}\frac{\alpha}{1+\alpha^2}-\color{red}{\frac{\log(1+\alpha)}{1+\alpha^2}}\ d\alpha$$ which simplifies to $$\color{red}{\int_0^1 \frac{\log(1+x)}{1+x^2}\ dx}= \frac{\pi \log 2}{16}-\color{red}{\int_0^1 \frac{\log(1+\alpha)}{1+\alpha^2}\ d\alpha}$$ hence the result $$\int_0^1 \frac{\log(1+x)}{1+x^2}\ dx=\frac{\pi \log 2}{8}.$$

  • $\begingroup$ That is a smarter way of doing it are you sure you meant $\frac{\log 2}{x}$? $\endgroup$ – Teh Rod May 18 '17 at 20:45
  • $\begingroup$ @TehRod that was a typo, now amended :) $\endgroup$ – user1892304 May 18 '17 at 20:51

Set $$x=\tan t, \qquad dt=\dfrac1{1+x^2}dx,$$ Then $$ \begin{align} \int_0^1 \frac{\ln(1+x)}{1+x^2}\, dx&= \int_0^{\pi/4} \ln(\cos t +\sin t)\, dt- \int_0^{\pi/4} \ln(\cos t)\, dt\\\\ &=\int_0^{\pi/4} \ln\left(\sqrt{2}\cos \left(\frac \pi4- t\right)\right)\, dt- \int_0^{\pi/4} \ln(\cos t)\, dt\\\\ &=\int_0^{\pi/4} \ln\left(\sqrt{2}\right)\, dt+\int_0^{\pi/4} \ln\left(\cos \left(\frac \pi4- t\right)\right)\, dt- \int_0^{\pi/4} \ln(\cos t)\, dt\\\\ &=\frac{\pi}8 \:\ln 2+\int_0^{\pi/4} \ln(\cos u)\, du-\int_0^{\pi/4} \ln(\cos t)\, dt\quad \left(u=\frac \pi4- t\right)\\\\ &=\frac{\pi}8 \:\ln 2. \end{align} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.